PREDICTABILITY TEST OF COMMODITY FUTURES PRICE INFORMATION ON INDONESIAN COMPOSITE STOCK PRICE INDEX VOLATILITY PERIOD 2007-2023 - Zidni, Muhammad Irfan; Irawan, Atika (PT Naureen Digital Education, 2023)
Indonesia is one of the nations that relies on commodities as the main driver of the economy. Commodities in Indonesia also have a role in the movement of composite stock price in Indonesia (IHSG). Therefore, we conducted research to find out which commodity price information can predict realized volatility (RV) from the IHSG. We use the linear regression model to determine the predictability of the commodity futures RV on the next month's RV of IHSG. We also conduct principal component analysis (PCA) and factor analysis (FA) to extract common factors from each commodity category dan semua komoditas. Our results show that commodities futures RV for Soybeans, Gold, Silver, Wheat and Cotton have a significant effect on the RV of IHSG with their is explaining the variability of IHSG RV predictions. Extracted common factors using PCA and FA from the types of commodities futures RV of Precious Metals, Grains, and Softs have a significant predictability for the RV of IHSG. All commodity futures extracted using PCA and FA also have the ability to predict the RV of the IHSG significantly. Average method can calculate more than PCA and FA method, meaning that average methods can predict more information about the types of commodity futures RV variances to the variability of IHSG RV.